2017
DOI: 10.1080/20008198.2017.1302652
|View full text |Cite
|
Sign up to set email alerts
|

Preventing PTSD with oxytocin: effects of oxytocin administration on fear neurocircuitry and PTSD symptom development in recently trauma-exposed individuals

Abstract: Background: Posttraumatic stress disorder (PTSD) is a debilitating psychiatric disorder which develops in approximately 10% of trauma-exposed individuals. Currently, there are few early preventive interventions available for PTSD. Intranasal oxytocin administration early posttrauma may prevent PTSD symptom development, as oxytocin administration was previously found to beneficially impact neurobiological (e.g. amygdala reactivity) and socio-emotional PTSD vulnerability factors. Objective: The overall aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 111 publications
3
44
0
1
Order By: Relevance
“…In PTSD patients, we showed sex-specific routes for the effects of single oxytocin administration on the potential to diminish anxiety (fear learning) and fear expression by the amygdala: increased inhibitory control of the vmPFC over the centromedial nucleus in men and fewer excitatory dorsal anterior cingulate cortex projections to the basolateral nucleus in women. So, while our findings add to accumulating evidence that oxytocin administration could potentially enhance treatment response in PTSD, the routes in men and women differ (Frijling, 2017). …”
supporting
confidence: 53%
See 1 more Smart Citation
“…In PTSD patients, we showed sex-specific routes for the effects of single oxytocin administration on the potential to diminish anxiety (fear learning) and fear expression by the amygdala: increased inhibitory control of the vmPFC over the centromedial nucleus in men and fewer excitatory dorsal anterior cingulate cortex projections to the basolateral nucleus in women. So, while our findings add to accumulating evidence that oxytocin administration could potentially enhance treatment response in PTSD, the routes in men and women differ (Frijling, 2017). …”
supporting
confidence: 53%
“…We hypothesized that the oxytocin system, which is associated with social support, fear and stress responses, was likely to play a sex-specific role in the stress response. In recently traumatized patients, we found that the effects of administration of oxytocin on amygdala reactivity to emotional stimuli depend on stimulus valence and sex (Frijling, 2017). In PTSD patients, we showed sex-specific routes for the effects of single oxytocin administration on the potential to diminish anxiety (fear learning) and fear expression by the amygdala: increased inhibitory control of the vmPFC over the centromedial nucleus in men and fewer excitatory dorsal anterior cingulate cortex projections to the basolateral nucleus in women.…”
mentioning
confidence: 99%
“…In humans, oxytocin delivered shortly after trauma 21,22 was reported to prevent the manifestation of the PTSD symptomatology. Indeed, the temporal contiguity between trauma and treatment suggests an acute effect of oxytocin on the neural support of a partially stabilized memory.…”
Section: Introductionmentioning
confidence: 99%
“…OT is a fundamental mediator of sociobehavioral processes, including social cognition (Crespi, 2016), interpersonal trust (Kosfeld et al, 2005;Baumgartner et al, 2008), anxiety (Missig et al, 2010), and stress response (Light et al, 2000;Cavanaugh et al, 2016), generating interest in OT as a potential therapeutic mediator of sociobehavioral deficits in conditions such as autism spectrum disorder (Andari et al, 2010;Anagnostou et al, 2012), post-traumatic stress disorder (Frijling, 2017;Sack et al, 2017), and schizophrenia (Pedersen et al, 2011;Brambilla et al, 2016). One major challenge is connecting pharmacologic signatures to sociobehavioral processes.…”
Section: Discussionmentioning
confidence: 99%